KONTRIBUSI PEREMPUAN PAPUA PENGRAJIN KERANG DALAM MENINGKATKAN PENDAPATAN RUMAHTANGGA DI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Maria Mayor; Ludia T. Wambrauw; Martua Hutabarat (Sosio Agri Papua, 2020)
Manokwari Regency has sufficient natural resource potential, one of which is marine natural resources which will greatly affect the economic conditions of the people if managed properly. This study aims to (1) Knowing the production and production costs of shell craft. (2) Determine the contribution of income from Papuan women in the shellfish business to family income in Manokwari Regency. The method used in this study is a qualitative method. The sampling technique is done by census. Data processing and analysis using tabulation. Based on the results of the study obtained an average of handicrafts produced by craftsmen from Manokwari is 39.08 units per month with a minimum number of products sold as many as 18 units and a maximum number of products sold as many as 70 units per month. And an average of handicrafts produced by craftsmen Biak origin is 40.33 units per month with a minimum number of products sold at 29 units and a maximum number of products sold at 47 units per month. The average production cost incurred shellfish craftsmen from Manokwari is Rp 1,185,000 per month with a minimum production cost of Rp 154,000 per month and a maximum production cost of Rp 1,890,000 per month and the average production cost incurred by craftsmen from Biak is Rp 1,493,833 per month with a minimum production cost of Rp 1,075,000 and a maximum production cost of Rp 2,175,000 per month. The average family income of shellfish entrepreneurs in respondents from Manokwari is IDR 3,007,500 per month and the contribution of shellfish business is 25.15% and the average family income for respondent from Biak is IDR 1,562,833 and contribution shellfish business is 26.05% and the income outside the shellfish business for respondents from Manokwari is Rp. 554,583 per month and income outside the shellfish business for respondents from Biak is Rp. 176,667. Per month. Women's involvement in decision making about allocating family income when making decisions about their household needs. Keywords: Potential Natural Resources, Manokwari, People's Economy, Shell Crafts, and Women Craftsmen.